Distribution and habitat use intensity of the Neotropical Otter (Lontra longicaudis) in a Colombian hydroelectric dam - Franco-Pérez, V (2020)
Introduction: The Neotropical Otter, Lontra longicaudis, is a semi-aquatic mammal that ranges from Mexico to Argentina inhabiting near-pristine watercourses, but also human-dominated aquatic and riparian landscapes. Objective: We assessed the distribution and habitat use frequency of L. longicaudis in La Miel I hydroelectric power dam and its influence area in the Department of Caldas, Colombia. Methods: We carried out diurnal surveys across standardized transects between 2014 and 2018 looking for records (sightings, faeces, tracks, and dens) that indicate the presence of the species. Each yearly survey was done during 12 consecutive days over three seasonal sampling periods assessing the upstream, reservoir, and downstream waterscape areas. Results: We sampled a total of 875 km in a five-year period across the three main waterscape areas (upstream -103 km, reservoir -582 km, and downstream -190 km) registering a total of 1 496 records. Faeces were the most common record (~ 95 %) across the whole study area followed by sightings, dens (1.7 % each), and tracks (1.3 %). Spatial distribution analyses suggest that L. longicaudis prefers dwelling upstream watercourses (hot spots areas; Gi Z-score = 4.46, p < 0.001) and in a lesser extent, areas around the water reservoir (cold spot areas; Gi Z-score = -2.69, p = 0.007). Signs of otters were also recorded at downstream area, but these records were non-significant within the analysis (Gi Z-score = -0.11, p = 0.48), suggesting L. longicaudis uses this area opportunistically. Cluster and outlier analysis showed that even though L. longicaudis was commonly found upstream and in the reservoir area, only some specific sectors (Moro, La Miel and Tasajos rivers) had high (LMI Z-score = 5.63, p = 0.001) and low (LMI Z-score = 2.12, p = 0.001) clusters. Conclusions: The upstream waterscape area is key for the survival of L. longicaudis in this regulated system, likely providing enough shelter and food for the species to carry out living activities and have resident populations. In contrast, downstream areas require specific attention to understand in a better way the effects of caused by the dam on the species dynamics, also defining management strategies that avoid population fragmentation and movement reduction.